Uma viagem pelo Data Mining com dados financeiros - Fernandes, S. Ribeiro (WICTA'2020 - 7th edition of WICTA, Special Interest Group on ICT for Auditing & Accounting, 2020)
Uma viagem pelo Data Mining com dados financeiros